(untitled) (MAUSAM, 1986)
Aerosol samples were collected at Pune and Srinagar during the month of May 1981 using the Staplex (USA) total suspended particulate matter (TSPM) sampler, Mass concentration as well as the various chemical constituents (water soluble fraction) of aerosols were obtained and the results of the above measurements are presented. Measurements show that TSPM at Pune owe their origin to both industrial and crustal (soil) sources whereas at Srinagar they are mainly of crystal origin and mass concentrations at both the places are similar. Study of correlation between NH, and SO, and ration of concentrations Indicate that good fraction of the above constituents existed in the form of (NH4)2. SO4 at Pune: At both the places, the balance between base and acids positive (base-acid) which suggests that, pH of rainwater at both the places would be In the basic range, This is substantiated also from pH data of rainwater which are available from Pune and Srinagar.